TUJUH CERITA RAKYAT DANAU SENTANI: TINJAUAN TEORI PARRY-LORD - Ummu Fatimah Ria Lestari (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This research about seven of Danau Sentani stories. This research discusses about 1) its formula on seven of Danau Sentani stories; 2) creating patterns on seven of Danau Sentani stories; and 3) Theory Parry-Lord applied on seven of Danau Sentani stories. Its goal is describing and analyzing the unsure and creating patterns on seven of Danau Sentani stories. This research used the qualitative and descriptive-analytics methods. Data was collected by documentation and interview technique. Data was analyzed by Parry-Lord methods. The results of this research are finding its structure that composed by formula, formulaic sentences, and theme. So we can say that Parry-Lord theory can be applied in folktale and myth genre.